Aspergillus sensitisation: an underappreciated treatable trait in airway disease. Issue 1 (5th January 2023) - Pollock, Jennifer; Chalmers, James D.
In 2006, Denning et al. [1] first proposed, in the European Respiratory Journal, the term "severe asthma with fungal sensitisation (SAFS)" to describe a distinct phenotype of severe asthma characterised by an elevated IgE-mediated response towards fungal allergens. Since then, SAFS has been widely studied and is generally considered to sit within a spectrum of disease ranging from uncomplicated asthma to frank allergic bronchopulmonary aspergillosis/mycosis (ABPA/ABPM) [2, 3]. Fungal sensitisation, particularly towards Aspergillus species, has been highlighted as a potential "treatable trait" in airway disease, with anti-fungal therapy and inhaled/oral corticosteroids forming the basis of treatment [2, 4, 5]. Sensitisation to Aspergillus is associated with increased exacerbations in patients with COPD http://bit.ly/3i4LVD9